In-depth study of spinal injuries from real world vehicle crashes in Saudi Arabia - Naif Khalaf Alshammari (19794165) (2015)
Effective injury mitigation measures can only be developed once a clear understanding of the problem has been obtained. The factors which contribute to the problem and hence the solution are based of analysis of real world data. The incidence of spinal injuries in traffic accidents has been identified to be a significant problem in Saudi Arabia and Gulf Countries (GCC). However, a detailed database, which could offer data from real world accidents, does not exist in this region from the world. Thus, the main aim of this study is to develop a sufficiently in-depth database, which can then be interrogated to address the problem of spinal injuries in Saudi Arabia. In this study, data on 778 spinal injuries (AIS ≥ 2) sustained by 552 casualties in 512 vehicle crashes collected from the city of Riyadh has been discussed and analysed. The primary crash factors, which might influence the occurrence and severity of spinal injuries, have been examined. In conclusion, the results obtained by this study can contribute significantly towards understanding the cause of spinal injuries and coming up with safety measures to mitigate them, especially in Saudi Arabia. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.50